Bacillus anthracis Prolyl 4-Hydroxylase Interacts with and Modifies Elongation Factor Tu - Schnicker, Nicholas J. (Biochemistry, 2017)
Prolyl hydroxylation is a very common post-translational modification and plays many roles in eukaryotes such as collagen stabilization, hypoxia sensing, and controlling protein transcription and translation. There is a growing body of evidence that suggests that prokaryotes contain prolyl 4-hydroxylases (P4Hs) homologous to the hypoxia-inducible factor (HIF) prolyl hydroxylase domain (PHD) enzymes that act on elongation factor Tu (EFTu) and are likely involved in the regulation of bacterial translation. Recent biochemical and structural studies with a PHD from Pseudomonas putida (PPHD) determined that it forms a complex with EFTu and hydroxylates a prolyl residue of EFTu. Moreover, while animal, plant, and viral P4Hs act on peptidyl proline, most prokaryotic P4Hs have been known to target free L-proline; the exceptions include PPHD and a P4H from Bacillus anthracis (BaP4H) that modifies collagen-like proline-rich peptides. Here we use biophysical and mass spectrometric methods to demonstrate that BaP4H recognizes full-length BaEFTu and a BaEFTu 9-mer peptide for site-specific proline hydroxylation. Using size-exclusion chromatography coupled small-angle X-ray scattering (SEC–SAXS) and binding studies, we determined that BaP4H forms a 1:1 heterodimeric complex with BaEFTu. The SEC–SAXS studies reveal dissociation of BaP4H dimeric subunits upon interaction with BaEFTu. While BaP4H is unusual within bacteria in that it is structurally and functionally similar to the animal PHDs and collagen P4Hs, respectively, this work provides further evidence of its promiscuous substrate recognition. It is possible that the enzyme might have evolved to hydroxylate a universally conserved protein in prokaryotes, similar to the PHDs, and implies a functional role in B. anthracis.